Cytotoxic screening and antibacterial activity of Withaferin A. Issue 16 (18th August 2022) - Rossato Viana, Altevir; Godoy Noro, B.; Lenz, J. C.; Luiza Machado Teixeira, M.; Bolson Serafin, M.; Hörner, R.; Franco, C.; Maria Fontanari Krause, L.; Stefanello Vizzotto, B.; Jalfim Maraschin, B.
ABSTRACT: Cancer and bacterial infections are among the leading causes of death worldwide. Plant-derived bioactive compounds constitute promising alternatives for development of new therapeutics. This study aimed at evaluating the biological activity of Withaferin A using 6 tumor cell lines: A549 (lung cancer), U87MG (glioblastoma), SH-SY5Y (neuroblastoma), B16-F10 (mouse melanoma), HeLa (uterine colon cancer) and K562 (chronic myeloid leukemia). In addition, 17 other standard bacterial strains and several multidrug resistant bacteria (MDR) clinical isolates were examined. Cell viability was assessed using the following assays: MTT, neutral red, and dsDNA PicoGreen®. Further, oxidative stress was measured by quantification of reactive oxygen species (ROS) production. The activity against bacteria was determined by the minimum inhibitory concentration (MIC), minimum bacterial concentration (CBM) and antibiofilm activity in the production of strains. Withaferin A was effective, as evidenced by its cytotoxic activity in tumor cell lines, enhanced ROS production in tumor cells and bactericidal and antibiofilm activity. Data demonstrated that Withaferin A may be therapeutically considered as an antitumor and antibacterial agent.